Tracking the underground river in the development of water resources in the karst areas - Heni Rengganis, Wawan Herawan, Wulan Seizarwati (Jurnal Sumber Daya Air)
Tracer technique is widely known as one of the methods used to find the relationship between the cave or underground river system in karst areas of South Blitar. In karst area of south blitar karst areas a number of water sources such as springs, underground river, and some streams out into the South Sea trace connections amongtracing the flow of underground river using tracer technique has been implemented with the aim to obtain data and information on flow systems around Umbul Tuk caves, so that water resources can be further developed as a value-added utilization of raw water supply in Blitar. Testing was conducted using artificial tracer material in the form of common salt NaCl and measurements were performed using a measuring instrument electrical conductivity (EC ). The measurement results indicate the existence of an underground river channel that connects Rowo with Umbul Tuk, with a flow rate of Umbul Tuk canal towards the South Sea of 360 l/s (March 2012), which has the potential to be exploited. Utilization of this flow, in addition to the needs of local people, and potentially also for fulfilling the needs of the new tourism in Pangi coast of the South Sea, which at present is still not developed.